Formation of the Vilsmeier-Haack complex: the performance of different levels of theory - Ozpinar, Gul Altinbas; Kaufmann, Dieter E.; Clark, Timothy (Journal of Molecular Modeling, 2011)
Because of discrepancies in the available experimental data, an extensive theoretical investigation of the formation of the Vilsmeier-Haack (VH) complex has been carried out. The barriers to complex formation calculated using eight different density functional methods (BLYP, B2-PLYP, B3LYP, B3PW91, MPW1K, M06-2X, and PBE1PBE), MP2, and extrapolation techniques (CBS-QB3, G3B3) with several basis sets (6 − 31 + G**, 6 − 311++G**, 6 − 311 + (3df,2p), aug-cc-pVDZ, and aug-cc-pVTZ) were compared with experimental data. For the overall reaction, MP2/aug-cc-pVDZ and M06-2X/6−31 + G(d,p) perform best compared to the CBS techniques. The results help clarify some open mechanistic questions.